Sustainability indicators models: synthesis and critical evaluation of the main experiences - Tayra, Flávio; Ribeiro, Helena (Saúde e Sociedade, 2006)
In this article, we made a synthesis, a categorization attempt and a critical evaluation of the main models, methodologies and experiences of construction of sustainability indicators, attempting to verify and to establish parameters and criteria in their constitution. At the present time, the main experiences developed around of the world can be classified in two types: 1) the systems of indicators, derived from the model of the Blue Book of the Commission of Sustainable Development of UN; and 2) the indicators synthesis, that aim, in a single unit, to join data of economical, biophysics, social and institutional order. Among such types of indicators, a great diversity of approaches is verified, with different emphasis. We discuss in this article the indicators' capacity to induce and to foment policies and structured well-based decisions.